2015
DOI: 10.1089/fpd.2014.1923
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Potential Effect of Morin in the Combination with β-Lactam Antibiotics Against Methicillin-Resistant Staphylococcus aureus

Abstract: Morin, a plant-derived flavonol, is known to be an effective inhibitor of Gram-positive bacteria. In this study, we explored the combined effect of morin with β-lactam antibiotics against methicillin-resistant Staphylococcus aureus (MRSA), a multidrug-resistant pathogen. The anti-MRSA activity of morin was investigated by the broth microdilution method, checkerboard dilution test, and time-kill curve assay. The expression of the resistant protein, penicillin-binding protein (PBP2a) encoded by mecA, was analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
(14 reference statements)
0
14
0
Order By: Relevance
“…Previous reports have suggested a number of flavonoids as possible modifiers of MRSA cell wall and cell membrane [ 18 , 19 , 20 ]. Moreover, several polyhydroxylated flavonoids have demonstrated considerable synergistic effect with β-lactams antibiotics [ 16 , 21 ], and PBP2a has been suggested as the possible target [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have suggested a number of flavonoids as possible modifiers of MRSA cell wall and cell membrane [ 18 , 19 , 20 ]. Moreover, several polyhydroxylated flavonoids have demonstrated considerable synergistic effect with β-lactams antibiotics [ 16 , 21 ], and PBP2a has been suggested as the possible target [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Morin ( 45 ) is well‐known to be effective against Gram‐positive bacteria. Combination of this plant‐derived flavonol with conventional β‐lactam antibiotics against MRSA showed that the susceptibility of MRSA toward oxacillin was enhanced significantly (Mun et al, ). Bioactive constituents from Croton menyharthii evaluated for their inhibitory effects on selected bacteria.…”
Section: Antibacterial Activity Of Flavonoidsmentioning
confidence: 99%
“…The resulting MIC for ampicillin was shifted from 800 to 107 μg/mL, and the MIC for ceftriaxone was shifted from 58 to 2.6 μg/mL. Similarly, Mun and colleagues also showed that a plant-derived flavonol, morin reversed the oxacillin-and ampicillin-treated MRSA [124]. Essential oils derived from Pituranthos chloranthus, Teucrium ramosissimum and Pistacia lentiscus also reduced the resistance of MRSA to various antibiotics in Penicillins' group such as amoxicillin, piperacillin, and oxacillin [125].…”
Section: Synergism Of Natural Products and Antibioticsmentioning
confidence: 87%
“…Mun and colleagues showed that the combination of morin and oxacillin synergistically killed the MRSA depending on the PBP2a-mediated resistance mechanism [124]. Another study demonstrated that the combination of ampicillin and Duabanga grandiflora extract inhibited the PBP2a protein [132].…”
Section: Penicillin-binding Protein 2a (Pbp2a)mentioning
confidence: 99%